The sentinel lymph node biopsy is an important part of diagnostic workup in skin melanoma patients - Nejc, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2003)
Background: Sentinel node biopsy allows for the detection of metastases to regional lymph nodes in the subclinical phase. Objective: Evaluation of the sentinel node detection rate with the use of pre-operative lymphoscintigraphy, intra-operative dye mapping and gamma radiation hand-held probe detection; determination of the occurrence of metastases in sentinel lymph node; evaluation of the incidence and type of complications of sentinel node biopsy in skin melanoma patients. Material and methods: From 1 December 1999 to 31 March 2003 in 160 skin melanoma patients sentinel node biopsy was performed. Patients with excised primary focus and without symptoms of regional and distant metastases were enrolled. There were 89 women (55.6%) and 71 men (44.4%) in the studied group (age range: 25–87). In all patients pre-operative lymphoscintigraphy, intra-operative dying and intra-operative detection of gamma radiation were performed. Identified sentinel nodes were removed for pathologic examination. Results: Pre-operative lymphoscintigraphy allowed for the detection of sentinel node in all studied patients. Sentinel nodes were detected intra-operatively in 157 patients (98.1%). Metastases in sentinel node were detected in 26/157 patients (16.6%). No intra-operative or post-operative complications were observed in 127 patients (79.4%). Conclusions: Sentinel node biopsy with the use of pre-operative lymphoscintigraphy, intra-operative dying and intra-operative detection of gamma radiation allow for the successful identification of sentinel node and detection of metastases in their subclinical phase. Sentinel node biopsy is a safe procedure.